VD_FINDINFO Jug / 2020 / 251 vom 19. September 2019 - VD Tribunal cantonal (2019)
VIOLATION DES RÈGLES DE LA CIRCULATION, CONDITIONS DE CIRCULATION | 29 LCR, 57 al. 2 OCR, 71a al. 4 OETV, 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH)